(untitled) (Kawalu: Journal of Local Culture, 2024)
Moslem scholars have accepted maqamat in reciting the Quran otherwise they have not accepted macapat as Javanese style in reciting the Quran such as recitation in the State Palace in commemoration of Isra` Miraj 2015. The paper uses a phonological approach to accents in Arabic and Javanese style in reciting the first verse of Surah Al-Isra`. The method used here is analysis of suprasegmental sound (accent) by using Speech Analyzer program and the comparison of these accents is analyzed by descriptive method. By doing so, the author found that: first, there is not any ideological reason to reject Javanese style because both of Arabic and Javanese style have some aspects suitable and unsuitable with Ilm Tajweed; second, the suitability of Arabic style was much than Javanese style; third, it is not right to reject reciting the Quran with Javanese style only based on assumption that it evoked mistakes and errors; fourth, the acceptance of Arabic style as the art in reciting the Quran should rised acceptance of the Javanese style also. So, rejection of reciting the Quran with Javanese style was not due to any reason and it could not be proofed by any logical argument.